Development of 1D Numerical Framework for Laser Induced Cavitation - Jabberi, Khalil (My University, 2022)
In this thesis work, we numerically investigate the life cycle of a laser induced cavitation. An in-house numerical tool is used and further developed. Simulations are carried out to model the growth and collapse of a vapor bubble in a superheated solution. The purpose behind this study is to increase our understanding of the bubble dynamics and the extreme physical conditions within and surrounding the laser induced cavity. The application of this work is within the field of laser induced crystallization, where the cavity serves as the crystal nucleation site. Proper modeling of all relevant physical phenomena is necessary to fully capture the right dynamics. The existing in-house code was developed for cavities induced by lower energy densities lasers. To extend the code to handle higher energy densities, often used in experimental studies, we identified the liquid compressibility and the formation of plasma to have significant effects. Different modeling techniques were implemented to account for a compressible liquid and simulations were performed to assess the effects of plasma formation. The developed numerical framework is able to produce qualitatively and quantitatively promising results for both thermo- and laser induced cavitation. The results suggest compressibility effects are of major importance during the formation and collapse of the bubble. The presence of plasma is also shown to be significant, particularly during the early stages of the growth phase. Our results are in fair agreement with both experimental and analytical data from literature. The reasons behind observed differences are discussed, and suggestions for future work and improvements are proposed. This thesis work can help better understand the underlying physics of laser induced cavitation and help industry to design an adequate environment for a well controlled crystallization.
Keywords: Crystallization; Laser Induced Cavity; Bubble Dynamics; Vapor Bubble; Numerical Framework; Compressible Liquid; Plasma formation